Pengaruh Ukuran Perusahaan, Diversifikasi Operasi, dan Diversifikasi Geografis terhadap Financial Distress - Naomi Nababan; Nuru Riani; Zulkarnain Zulkarnain (Prodi Akuntansi FE Universitas Maritim Raja Ali Haji, 2022)
This study was conducted to obtain empirical evidence of the effect of firm size, operating diversification, and geographic diversification on financial distress. The research sample is Textile and Garment Sub-sector companies listed on the Indonesia Stock Exchange for the 2016-2019 period. The sample selection technique used purposive sampling method with predetermined criteria, to obtain a sample of 15 companies with four periods and a total of 60 observations. Data analysis used logistic regression analysis with SPSS version 25 software. The results showed that company size, operating diversification, and geographical diversification had no effect on financial distress.